Improving the Fire Resistance Efficiency of Dielectric Materials (Eurasian Journal of Engineering and Technology, 2023)
The fire resistance properties of dielectric materials play a critical role in ensuring the safety and reliability of electrical systems. This article presents a comprehensive review of various strategies and techniques employed to enhance the fire resistance efficiency of dielectric materials. The aim is to provide researchers, engineers, and material scientists with a comprehensive understanding of the current advancements in this field. The article covers key aspects such as fire retardant additives, nanostructured materials, composite formulations, and surface modification techniques. Additionally, recent advancements and challenges in the development and characterization of fire-resistant dielectric materials are discussed. This review will serve as a valuable resource for further research and development in this area